Turbo: energy efficient air blower - Anderson, Ibar Federico (2021)
The project consists of the design by electromechanical simulation by NI Multisim 14.0 software, re-design of the casing by CAD by Cfturbo 2020 R2.0 + SketchUp Pro 2017 software and rapid 3D prototyping by ABVieber 14.0 software + OverLord Pro 3D printer; for the design of a prototype centrifugal air blower for civil and commercial (non-industrial) use. The proposal corresponds to a single-phase alternating current (AC) motor electromechanically simulated by analogy with a bipolar stepper motor (Stepper) reconfiguring as a synchronous motor. Design developed with the Design Thinking methodology within the Project (Code: B374) located in the Secretariat of Science and Technology (SCyT-FBA-UNLP) of the National University of La Plata, Department of Industrial Design. Whose title is: «Integrated Management of Design and Innovation. Contributions for a theoretical-conceptual and methodological review» is in charge of the Director: Mg. Federico del Giorgio Solfa. The “Turbo: eco-blower-air” project aims to link the secondary level (Technical High School of the Argentine Republic) with the University system of the Argentine Republic (Technological profile careers), create development ties so that future graduates value the need and usefulness of knowledge with technological profiles of Industrial Design, Research + Technological Development (R&D), as described in the new Law of the Knowledge Economy (Law No. 27,570). The work led to two previous publications: “Energy efficiency improvements (EE) in single-phase synchronous motors of 220 (VAC) / 50 (Hz), type PMSM”, in the UIS Ingenierías magazine, Faculty of Engineering of the Universidad Industrial Santander (Colombia); and “Eco-turbine. Electric turbo fan 200 (VAC) - 50 (Hz), low consumption: energy efficient” from the magazine Innovation and Technological and Social Development of the National University of La Plata (Argentina). For more information see bibliography.